Perkembangan UMKM di Provinsi Jawa Barat pada Tahun 2020-2022 Dengan Pendekatan Statsitik Deskriptif - Nurlaila, Lela; Febrian, Muhammad Egi; Agustian, Muhammad Helmi; Ramdhan, Muhammad Luthfi; Fahira, Nabila Zumar; Paujiah, Ninda Nabila; Wardiah, Mia Lasmi (Melati Institute, 2024)
This study aims to examine the development of Micro, Small, and Medium Enterprises (MSMEs) in West Java Province during the 2020-2022 period. MSMEs have a function in the region by increasing employment opportunities, raising residents' income, and facilitating economic development. Secondary data from the Central Bureau of Statistics (BPS) and the West Java Office of Cooperatives and MSMEs were used in this study. Descriptive statistical methods are used to illustrate the growth trend in the number of MSMEs, dominant business sectors, geographical distribution, and contribution to regional GDP.The results show an increase in the number of MSMEs in West Java during this period, despite the CORONA pandemic having a profound effect on their operations and income. The trade and services sector is the most dominant sector in MSME growth, while the distribution of MSMEs is more concentrated in urban areas compared to rural areas. The study also found that MSMEs in West Java contribute significantly to the regional economy, although they still face various challenges such as access to capital, technology and markets.The conclusion of this study highlights the importance of government support through policies that support access to capital, capacity building, and market access for MSMEs. Policy recommendations include providing incentives, training programs, and facilitating market access through digitalization and online platforms. This research is expected to be a resource for policy makers and related parties in an effort to advance the MSME sector in West Java.